Pengaruh Manajemen Peserta Didik Sekolah Menengah Pertama terhadap Prestasi Belajar - Nailatsani, Fathinahaya; Setiawan, Farid; Aryulina, Diah Anita; Husaini, Aldi Al; Harjanti, Ghaida Yasmin Nur (Lembaga Yasin AlSys, 2021)
School management is one of the processes to achieve a school atmosphere so that teaching and learning activities can take place effectively and efficiently. Good school management will increase the motivation of educators, but problems will occur if this is seen from the room arrangements and school conditions that are not so good. In the world of education, the notion of quality in the context of educational outcomes refers to the achievements of school students. The achievements achieved by students are non-academic and academic achievements. This research is a literature study research technique where the results of the discussion are the results of references to books, journals, articles that are appropriate or related to this discussion. Looking for various information from books, journals, articles and realities of problems that fit the discussion into one, then reviewed again with grammar and ways to become interesting information. In this article, we will discuss the management of educator achievements in junior high schools, management of junior high school students in Indonesia, the influence of management for junior high school students on learning achievement.